MC-LR Aggravates Liver Lipid Metabolism Disorders in Obese Mice Fed a High-Fat Diet via PI3K/AKT/mTOR/SREBP1 Signaling Pathway - Hanyu Chu; Can Du; Yue Yang; Xiangling Feng; Lemei Zhu; Jihua Chen; Fei Yang (Toxins, 2022)
Obesity, a metabolic disease caused by excessive fat accumulation in the body, has attracted worldwide attention. Microcystin-LR (MC-LR) is a hepatotoxic cyanotoxin which has been reportedly to cause lipid metabolism disorder. In this study, C57BL/6J mice were fed a high-fat diet (HFD) for eight weeks to build obese an animal model, and subsequently, the obese mice were fed MC-LR for another eight weeks, and we aimed to determine how MC-LR exposure affects the liver lipid metabolism in high-fat-diet-induced obese mice. The results show that MC-LR increased the obese mice serum aspartate aminotransferase (AST) and alanine aminotransferase (ALT), indicating damaged liver function. The lipid parameters include serum triglyceride (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-c), and liver TG, which were all increased, whilst the high-density lipoprotein cholesterol (HDL-c) was decreased. Furthermore, after MC-LR treatment, histopathological observation revealed that the number of red lipid droplets increased, and that steatosis was more severe in the obese mice. In addition, the lipid synthesis-related genes were increased and the fatty acid β-oxidation-related genes were decreased in the obese mice after MC-LR exposure. Meanwhile, the protein expression levels of phosphorylation phosphatidylinositol 3-kinase (p-PI3K), phosphorylation protein kinase B (p-AKT), phosphorylation mammalian target of rapamycin (p-mTOR), and sterol regulatory element binding protein 1c (SREBP1-c) were increased; similarly, the p-PI3K/PI3K, p-AKT/AKT, p-mTOR/mTOR, and SREBP1/β-actin were significantly up-regulated in obese mice after being exposed to MC-LR, and the activated PI3K/AKT/mTOR/SREBP1 signaling pathway. In addition, MC-LR exposure reduced the activity of superoxide dismutase (SOD) and increased the level of malondialdehyde (MDA) in the obese mice’s serum. In summary, the MC-LR could aggravate the HFD-induced obese mice liver lipid metabolism disorder by activating the PI3K/AKT/mTOR/SREBP1 signaling pathway to hepatocytes, increasing the SREBP1-c-regulated key enzymes for lipid synthesis, and blocking fatty acid β-oxidation.